2013
DOI: 10.1021/jp401770e
|View full text |Cite
|
Sign up to set email alerts
|

Toward Organic Photohydrides: Excited-State Behavior of 10-Methyl-9-phenyl-9,10-dihydroacridine

Abstract: The excited-state hydride release from 10-methyl-9-phenyl-9,10-dihydroacridine (PhAcrH) was investigated using steady-state and time-resolved UV/vis absorption spectroscopy. Upon excitation, PhAcrH is oxidized to the corresponding iminium ion (PhAcr(+)), while the solvent (acetonitrile/water mixture) is reduced (52% of PhAcr(+) and 2.5% of hydrogen is formed). The hydride release occurs from the triplet excited state by a stepwise electron/hydrogen-atom transfer mechanism. To facilitate the search for improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…Subsequently, we probed the 1H + /2e – reactivity of 1 H – with two different hydride acceptors. The reaction of in situ generated 1 H – with 1.0 equiv of the acridinium hydride acceptor Ph-Acr + at 25 °C in MeCN- d 3 afforded 1 concomitant with the formation of Ph-AcrH (Figure and Figure S28; [Ph-Acr]­ClO 4 = 10-methyl-9-phenyl­acridinium perchlorate, Δ G ° H – = 76 kcal mol –1 in MeCN) . Monitoring of the reaction progress by 1 H NMR spectroscopy using the internal standard 1,3,5-trimethoxy­benzene showed that the reaction was almost completed after 3 h at 25 °C and proceeds with 90% spectroscopic yield (Figure S22).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we probed the 1H + /2e – reactivity of 1 H – with two different hydride acceptors. The reaction of in situ generated 1 H – with 1.0 equiv of the acridinium hydride acceptor Ph-Acr + at 25 °C in MeCN- d 3 afforded 1 concomitant with the formation of Ph-AcrH (Figure and Figure S28; [Ph-Acr]­ClO 4 = 10-methyl-9-phenyl­acridinium perchlorate, Δ G ° H – = 76 kcal mol –1 in MeCN) . Monitoring of the reaction progress by 1 H NMR spectroscopy using the internal standard 1,3,5-trimethoxy­benzene showed that the reaction was almost completed after 3 h at 25 °C and proceeds with 90% spectroscopic yield (Figure S22).…”
Section: Resultsmentioning
confidence: 99%
“…The radical [XNCH 3 ] • in Figure S26a displays strong enough red-shifted absorption bands relative to its triflate salt [XNCH 3 ] + to color the cuvette solution orange and weak absorption bands past 550 nm. 27,32 The accumulation of orange-colored [XNCH 3 ] • can be reproduced by addition of either metallic Zn or SmI 2 /THF under Ar. The SEC of [X O] + and [XS] + in Figure S26b,c produces blue-shifted absorption bands relative to their triflate salts and similar weak absorption bands past 550 nm.…”
Section: And [Xs]mentioning
confidence: 99%
“…In the nearly 100 years since that time, these radicals have been implicated as intermediates in numerous systems for the study of potential NADH/NAD + analogues, , catalytic photo-oxidants, and hydrogen evolution catalysts . Their one-electron oxidized counterparts, the cations 10-methyl-9-phenylacridinium [ XNCH 3 ] + , 9-phenylxanthenium [ XO ] + , and 9-phenylthioxanthenium [ XS ] + , shown in Scheme , are interesting in their own rights as intermediates in turn-on fluorescent photo- and electrochromic switches, excited-state photohydrides and photobases. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…meaning it measures the free energy difference before and after a hydride transfer reaction. Hydride transfer reactions play a crucial role in various renewable energy technologies, such as the electrochemical reduction of CO 2 into carbon-based fuels [1,2,3,4,5,6] or H 2 synthesis [4,7].…”
Section: Introductionmentioning
confidence: 99%